Pengaruh Intensitas Aset Tetap dan Reputasi Auditor terhadap Manajemen Pajak Perusahaan pada Perusahaan Bidang Kesehatan yang Terdaftar di BEI - Mabrian, Ayu Maretha; Anik, Sri (Innovative: Journal Of Social Science Research, 2025)
Tax management Issues related in healthcare sector companies persist. That’s a result of the impact of fixed asset intensity and auditor reputation. This research to assess impact of fixed asset intensity and auditor reputation on tax management within health sector listed on IDX. This research is explanatory. The population comprises health sector listed on the IDX from 2019 to 2024, the sample selection technique employed is purposive sampling, resulting in total of 60 samples. The analysis method used is t tests and F tests. The t test indicates that the intensity of fixed assets has significant positive impact on tax management (P=0.001), and the reputation of auditors also has significant positive influence on tax management (P=0.042). The F test has significance value of 0.047. The findings of this research indicate that both fixed asset intensity and auditor reputation can collectively influence tax management in health sector listed on the IDX.